Effect of abutment excitation on bridge pounding - Li, B.; Bi, Kaiming; Chouw, N.; Butterworth, J.; Hao, Hong (Pergamon, 2013)
Bridge damage due to pounding at joints of girders and abutments has been observed in many major earthquakes. One reason that this pounding phenomenon is so common is due to the differences between the dynamic characteristics of a girder and the relatively rigid adjoining abutments. Hence, a good understanding of girder-abutment pounding is critical for bridge design. However, the studies on this topic have mainly been numerical and abutment excitation was rarely considered. Very limited experimental investigations were conducted, none of which considered the effect of abutment motion on bridge pounding response. The objective of this study is to experimentally evaluate the influence of abutment excitations on the pounding behaviour of a system consisting of a single bridge span with various fundamental frequencies and its abutments using three shake tables. The excitations are applied in the longitudinal direction of the bridge span. The spatially varying ground excitations are simulated based on the New Zealand design spectra for soft soil, shallow soil and strong rock conditions using an empirical coherency loss function. Results show that with the spatial variation effect of ground motions, a consideration of movable rather than fixed abutments leads to greater relative opening displacement with its adjacent structure and larger pounding potential.